Improving Na/Na3Zr2Si2PO12 Interface via SnOx/Sn Film for High‐Performance Solid‐State Sodium Metal Batteries. Issue 9 (1st August 2021) - Yang, Jiayi; Xu, Henghui; Wu, Jingyi; Gao, Zhonghui; Hu, Fei; Wei, Ying; Li, Yuyu; Liu, Dezhong; Li, Zhen; Huang, Yunhui
Abstract: Sodium (Na) metal batteries have attracted much attention due to their rich resources, low cost, and high energy density. As a promising solid electrolyte, Na3 Zr2 Si2 PO12 (NZSP) is expected to be used in solid‐state Na metal batteries addressing the safety concerns. However, due to the poor contact between NZSP and the Na metal, the interfacial resistance is too large to gain proper performance for practical solid‐state batteries (SSBs) application. Here, a SnO x /Sn film is successfully introduced to improve the interface between Na and NZSP for enhancing the electrochemical performance of SSBs. As a result, the Na/NZSP interfacial resistance is dramatically reduced from 581 to 3 Ω cm 2 . The modified Na||Na symmetric cell keeps cycling over 1500 h with an overpotential of 40 mV at 0.1 mA cm –2 at room temperature. Even at current densities of 0.3 and 0.5 mA cm –2, the cell still maintains an excellent cyclability. When coupled with NaTi2 (PO4 )3 and a Na3 V2 (PO4 )3 cathode, the full‐cell demonstrates a good performance at 0.2 C and 1 C, respectively. The present work provides an effective way to solve the interface issue of SSBs. Abstract : SnO x /Sn film is introduced on the surface of Na3 Zr2 Si2 PO12 (NZSP) to improve the interface contact and reduce the resistance between Na and NZSP. As a result, the Na/NZSP interfacial resistance is dramatically reduced from 581 to 3 Ω cm 2 . The Na||Na symmetric cell with SnO x /Sn‐modified NZSP cycles stably over 1500 h at room temperature.